Abstracts from the 2019 Research Poster Session at the American Massage Therapy Association Annual Convention - Kennedy, LMT, BCTMB, DrPH, Ann Blair (International Journal of Therapeutic Massage & Bodywork, 2020)
The 2019 Poster Session at the American Massage Therapy Association National Convention included the following 6 posters as well as the posters presented at the International Massage Therapy Research Conference (IMTRC). The abstracts from IMTRC can be found also at the IJTMB (https://ijtmb.org/index.php/ijtmb/article/view/495).